Recommendations for cardiomyopathy surveillance for survivors of childhood cancer: a report from the International Late Effects of Childhood Cancer Guideline Harmonization Group. Issue 3 (March 2015) - Armenian, Saro H; Hudson, Melissa M; Mulder, Renee L; Chen, Ming Hui; Constine, Louis S; Dwyer, Mary; Nathan, Paul C; Tissing, Wim J E; Shankar, Sadhna; Sieswerda, Elske; Skinner, Rod; Steinberger, Julia; et al.
Summary Survivors of childhood cancer treated with anthracycline chemotherapy or chest radiation are at an increased risk of developing congestive heart failure. In this population, congestive heart failure is well recognised as a progressive disorder, with a variable period of asymptomatic cardiomyopathy that precedes signs and symptoms. As a result, several clinical practice guidelines have been developed independently to help with detection and treatment of asymptomatic cardiomyopathy. These guidelines differ with regards to definitions of at-risk populations, surveillance modality and frequency, and recommendations for interventions. Differences between these guidelines could hinder the effective implementation of these recommendations. We report on the results of an international collaboration to harmonise existing cardiomyopathy surveillance recommendations using an evidence-based approach that relied on standardised definitions for outcomes of interest and transparent presentation of the quality of the evidence. The resultant recommendations were graded according to the quality of the evidence and the potential benefit gained from early detection and intervention.